Adipose transcriptome in the scalp of androgenetic alopecia - Cruz, Criselda Jean G.; Hong, Yi-Kai; Aala, Wilson Jr. F.; Tsai, Ren-Yeu; Chung, Pei-Lun; Tsai, Yau-Sheng; Hsu, Chao-Kai; Yang, Chao-Chun (Frontiers in Medicine, 2023)
Earlier studies have shown how adipocytes can modulate the activity of hair follicle stem cells. Meanwhile, the role of adipocytes in the pathogenesis of androgenetic alopecia (AGA) remains unknown. We aim to determine signaling pathways related to the adipose tissue changes in the human scalp with AGA through RNA-seq analysis. RNA was isolated from the adipose tissues derived from the bald (frontal) and normal (occipital) scalp of male patients with AGA (n=4). The pooled RNA extracts from these samples were subjected to RNA sequencing followed by differential gene expression and pathway analysis. Our gene expression analysis identified 1060 differentially expressed genes, including 522 upregulated and 538 downregulated genes in the bald AGA scalp. Biological pathways pertaining to either adipose tissue metabolism or the hair cycle were generated in our pathway analysis. Downregulation of the peroxisome proliferator activated receptor (PPAR) signaling pathway was noted to be significant in the bald scalp. Expression of adipogenic markers (e.g., PPARG, FABP4, PLN1, and ADIPOQ) was also decreased in the bald site. These findings imply that adipogenesis becomes downregulated in AGA, specifically within the bald scalp adipose. Our results lead to a hypothesis that PPAR-mediated adipogenesis in the scalp adipose, via crosstalk with signaling pathways involved in hair cycling, might play a role in AGA.